Os ritmos e a produção do espaço de Jataí (GO) : do rural ao urbano - Oliveira, Eliardo Miranda (2021)
Jataí is a municipality located in the southwestern portion of the state of Goiás and its emergence was rooted in the expansion of agricultural activities. Since its formation, it has undergone numerous changes that impacted the growth rates of both rural and urban spaces, also reflecting on the lives of its population. Given the context explained, this study sought to understand the production and reorganization of space in the municipality of Jataí-GO, with a view to identifying the factors related to the distribution and concentration of rural and urban properties, taking into account the use of rural land and the conditioning agents for real estate speculation and urban segregation present in Jataí. For this, a bibliographical research on the subject was carried out, which subsidized the theoretical discussions and supported many data presented throughout this study. Therefore, it was based on authors such as Lefebvre (1993), Côrrea (2003), Melo (2003), Silva (2005), Silva (2009), Silva (2011), Tarifa and Sette (2012), Moureaux (2013), Fonseca (2014), Oliveira (2016), Portela and Tarifa (2017), among others. In addition, a survey of quantitative data was carried out with the IBGE, SICAR, EMBRAPA, the City Hall of Jataí, among others. This study allowed us to verify that there were many changes that the city has undergone since its formation until the present day. Among these changes, one can start by dealing with the environmental issue: between the 1960s and 2018, Jataí had a drastic reduction in its natural vegetation, directly affecting the local fauna and flora. While in the mid-1960s the native vegetation made up 47.48% of the total area of the municipality, in the period of 2018 it started to make up only 9.76%, extending into small patches, mainly close to water bodies. This reduction in the areas of native vegetation was accompanied by the expansion of agricultural activities and also by the population growth of Jataí. Still in relation to the Jataiense soil, it was identified that, in 2020, 99.49% of it was composed of rural areas, which are still concentrated in the hands of a few. In this regard, it was found that in 2010 some groups still owned most of the rural properties in Jataí, among which were the surnames linked to the pioneer families Carvalho and Vilela, who owned, in that period, 23.88% and 4.48% of rural properties, respectively. As for the control of urban properties, it was identified that these surnames occupied the seventh and twentieth position, respectively. Regarding the accumulation ranges of urban properties in Jataí, it was possible to verify that these surnames were in 1st and 8th place. Thinking about the spatialization of different properties in the urban space of Jataí, it became evident that the noblest properties, that is, those aimed at the population with a better income, are located in strategic points of the city, namely: places with higher and lower altitudes slopes. These points, in addition to having a better infrastructure, have the characteristics of having higher sales values, limiting their access and their audience. On the other hand, the places with the highest slopes and with the lowest altitudes, in general, have lower venal values and are, therefore, the spaces where low-income populations reside. In view of this, it was observed that socio-spatial segregation is present in Jataí, requiring the development of public policies that minimize this economic and social dichotomy observed in the municipality and which is increasingly responsible for the increase in poverty, prejudice and social exclusion.